The Just and Pope Model of Production Risk in Turmeric Farming at the Kesamben Wetan Farmers’ Group Association, Driyorejo District, Gresik Regency: Model Just and Pope pada Risiko Produksi Usahatani Kunyit di Gapoktan Kesamben Wetan Kecamatan Driyorejo Kabupaten Gresik - Diky Yulianto; Noor Rizkiyah; Wahyu Santoso (Jurnal Ilmiah Sosio Agribis, 2026)
This study aims to analyze the influence of production factors on production risk in turmeric farming within the Kesamben Wetan Farmers Group, located in Driyorejo District, Gresik Regency. Turmeric is a high-value commodity that serves as a key raw material for the pharmaceutical industry and Indonesia’s spice exports. However, in recent years, turmeric production in Gresik Regency has declined due to unstable yields and fluctuations in production factors. The study employs a quantitative approach using the Just and Pope model and the Cobb-Douglas production function to analyze the relationship between production inputs and production risk, utilizing SPSS 25 software. A total of 76 farmers were selected through proportionate stratified random sampling from members of the Kesamben Wetan Farmers’ Association. The analyzed variables include land area, seed quantity, organic fertilizer, urea fertilizer, and labor. The results indicate that land area, organic fertilizer, and urea fertilizer have a positive effect on production risk (risk inducing factors), while seed quantity and labor have a negative effect (risk reducing factors). The coefficient of determination (R²) value of 0.646 in the risk (variance) model indicates that 64.6% of the variation in production risk can be explained by the production factors included in the model. The findings suggest that efficient use of inputs, particularly seeds and labor, plays an important role in reducing production risk, while the use of land and fertilizers should be managed more proportionally to prevent increased production risk.